Analysis of b-Value and Peak Ground Acceleration (PGA) in West Sumatra Province using Maximum Likelihood Method and Empirical Formula (Earthquake data Period 2007-2020) - Fandu Alfadilah; - Syafriani; - Hamdi; Letmi Dwiridal; Fajri Syukur Rahmatullah (PILLAR OF PHYSICS, 2022)
West Sumatra Province has four active fault segments, namely part of the Sumatran fault zone which causes frequent earthquakes. Therefore, it is necessary to research b-value analysis and PGA in the province of West Sumatra by using the maximum likelihood method and empirical formula for earthquake disaster mitigation efforts. This study aims to determine the b-value associated with rock stress and PGA as the level of earthquake activity and analyze the distribution map. The data used is earthquake data for the period 2007-2020 with a magnitude ≥ 5 SR and a depth of ≤ 100 km. The results of data processing produce a map of the distribution of b-value and PGA in the province of West Sumatra. The b-value in each region ranged from 0.8421-1.4477. Based on the b-value distribution map, the area that has the smallest b-value is in region 6, while the largest value is in region 2. A low b-value correlates with high rock stress conditions. This value illustrates that area 6 has a high chance of a major earthquake occurring. Furthermore, the calculation of the PGA value refers to the general form of Lin and Wu's empirical equation to obtain a new empirical formula model. The value of the coefficient a=−1.20543, b=−0.839093, and c=6.88858. The PGA value of West Sumatra province ranges from 10.87-376.98 gal. The city/regency with the largest PGA value is in the Mentawai Islands Regency, which ranges from 84.11-328.17 gal and the lowest value is in Dharmasraya Regency, which is between 10.87-35.28 gal.